Evidence for dark matter in the inner Milky Way - Iocco, Fabio [UNESP]; Pato, Miguel; Bertone, Gianfranco (Nature Publishing Group, 2015)
The ubiquitous presence of dark matter in the Universe is today a central tenet in modern cosmology and astrophysics(1). Throughout the Universe, the evidence for dark matter is compelling in dwarfs, spiral galaxies, galaxy clusters as well as at cosmological scales. However, it has been historically difficult to pin down the dark matter contribution to the total mass density in the Milky Way, particularly in the innermost regions of the Galaxy and in the solar neighbourhood(2). Here we present an up-to-date compilation of Milky Way rotation curve measurements(3-13), and compare it with state-of-the-art baryonic mass distribution models(14-26). We show that current data strongly disfavour baryons as the sole contribution to the Galactic mass budget, even inside the solar circle. Our findings demonstrate the existence of dark matter in the inner Galaxy without making any assumptions about its distribution. We anticipate that this result will compel new model-independent constraints on the dark matter local density and profile, thus reducing uncertainties on direct and indirect dark matter searches, and will help reveal the structure and evolution of the Galaxy.